The relationship between socio-demographic and midwifery factors with delay in seeking help for genital warts patients - Seyedeh Maryam Attari; Narges Alizadeh; Seyedeh Hajar Sharami; Seyedeh Fatemeh Dalil Heirati; Roya Kabodmehri; Elahe Rafiei (Mashhad University of Medical Sciences, 2022)
Introduction: It is important to timely refer in order to diagnosis and treatment of genital warts and preventing disease transmission. Therefore, identifying the socio-demographic and obstetric effective factors is important in the delay of patient's seeking-help. The present study was performed aimed to investigate the relationship between demographic, social and obstetric factors with seeking-help delay in patients with genital warts. Methods: This descriptive-analytical study was performed in 2019 on 130 women with genital warts referred to the gynecology clinic of Al-Zahra Hospital in Rasht. Inclusion criteria were confirmation of the diagnosis of genital wart based on clinical examination and laboratory tests and a maximum of six months after diagnosis. Data collection tools included socio-demographic form, midwifery form and a researcher-made questionnaire to assess patient's delay. A delay of more than 7 days in referral for definitive diagnosis and treatment was considered as a delay in patient's seeking help. Data were analyzed by SPSS software (version 21) and Chi-square, Fisher, Mann-Whitney tests and logistic regression. P<0.05 was considered statistically significant. Results: Among 130 participant, 94 (72%) had more than 7 days delay. There was statistically significant difference between the two groups in the variables of history of abortion, type of first diagnostic symptom and type of treatment received (P<0.05). Logistic regression analysis showed that the variables of history of gynecological infection (CI 95%: 1.08-9.40, OR=3.187), type of residence place (economic status) (CI 95%: 1.02-9.31, OR=3.08) and history of abortion (CI 95%: 1.30-15.63, OR=4.51) have a predictive role in help-seeking delay. Conclusion: There is a relationship between the variables of history of gynecological infection, economic status and history of abortion with delay in seeking help for diagnosis and treatment of genital warts. Therefore, health care providers should be more careful in dealing with and educating low socioeconomic status women, patients with a history of infection and women without experience of abortion and nulliparous.